The value of visual inspection with acetic acid and Pap smear in cervical cancer screening program in low resource settings - A population-based study - Nguyen Vu Quoc Huy; Le Minh Tam; Ngo Viet Quynh Tram; Dang Cong Thuan; Truong Quang Vinh; Cao Ngoc Thanh; Linus Chuang (Elsevier, 2018)
This study aims to determine the diagnostic values of visual inspection with acetic acid (VIA) and Pap smear in a cervical cancer screening program at a community level in Vietnam. A cross-sectional analysis was obtained, including 1034 women of reproductive age from Thua Thien Hue Province, Vietnam from 09/2012 to 09/2013. Samples were taken from cervixes for Pap smear testing, followed by visual inspection with acetic acid. Subjects with abnormal VIA and/or positive cytology results were invited for colposcopy and biopsy. Histologic confirmed cervical intraepithelial neoplasia (CIN2+) served as gold standards for diagnostic values analysis. Abnormal VIA results were recorded in 87 cases (7.7%). The sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) of VIA for CIN2+ were 88.8%, 43.8%, 63.4%, 51.2% and 83.3%, respectively. Diagnostic values of Pap smear were 58.0%, 85.2%, 69.9%, 83.3% and 61.3% for its sensitivity, specificity, accuracy, PPV and NPV, respectively. VIA yielded high sensitivity but its accuracy is still limited in pre-cancerous lesions during cervical cancer screening. The Pap smear has acceptable sensitivity and specificity, but its false-negative rate is still high. We recommend a combination of different tests to increase the efficiency of screening in our community. Keywords: VIA, Pap smear, Cervical cancer screening